Reaction of radiometric parameters to atmospheric pollution: Part I - Variation over time - DESIKAN , V.; CHIVATE, V. R.; ABIHYANKAR, V. V. (MAUSAM, 1994)
The drive for indust rial development h... ... 100 to large scale urbanisation and result,.-. d in the injec tion of good amount of suspended particle.. and gaseous substances into the atmosphere. The m..er-abusc of the capac ity .of the atmosphere to sustain the equilibrium is bound to disturb the heal budget of the earthatmosphere system. Radiometric parameters of the atmosphere give an early indication of the trends in the longterm climatic changes. Whi le the global rad iant exposure is no t likely to show perceptible changes due to the increased scauering by the pollutants, I diffuse radiant el(p(ls re and the direct so.l3! irradianc respond qu ickly to the changes In the atmospheric conditions. Various controlling factors like humidity. soi l moist ure and cloud" have d ifferent effects on the terres trial radiant energy and the changes in thi s energy OI..’Cur slowly and ta ke long time to affect the climate at a place. But the general trend is indicated by the increased diffuse component in the di rect sola r rrmdiances and in the net outgoing terrestrial radia nt energy. The responses arc clearly indicative. part icularly ,II Punc......here the industrial activiti es grew at a phenomenal rate during the past fifteen years.